Short-term pain for long-term gain? A longitudinal meta-analysis of downsizing-financial performance relationships - Steel, Piers; House, Alyson (Frontiers in Behavioral Economics, 2024)
Introduction Downsizing, and the mass layoff upheavals that ensue, has been euphemistically referred to as a short-term pain, long-term gain strategy. But is that so? Do its financial outcomes over time justify the short-run harm? And, to what extent has its adoption been driven by economic or social rationales over time? Methods To examine these questions, we conducted the most comprehensive meta-analysis on downsizing-financial performance relationships to date, summarizing a total of 905 effect sizes. Using a new meta-analytic method multi-level longitudinal meta-analysis (MLLMA) we analyze temporal dimensions of these relationships. Results Results for downsizing adoption suggest shifting rationales over time, from a defensive response to decline in the 1980s, to a socially legitimate management convention in the 1990s, and back to a defensive response in the 2000s. Short-run market outcomes mirror these shifting rationales, with more negative reactions to defensive downsizing. Across a diverse range of lead/lag times and moderators, we find many negative and heterogeneous performance outcomes. Most importantly, little long-term gain is found. Discussion Our MLLMA helps to address prior criticisms on the lack of temporality in extant downsizing research, while many equivocal relationships, despite almost 40 years of downsizing research, illustrate that considerable avenues for future research remain.